Low-Temperature Chemical Vapor Deposition Growth of MoS2 Nanodots and Their Raman and Photoluminescence Profiles - Mawlong, Larionette P. L.; Biroju, Ravi K.; Giri, P. K. (Frontiers in nanotechnology, 2021)
We report on the growth of an ordered array of MoS 2 nanodots (lateral sizes in the range of ∼100–250 nm) by a thermal chemical vapor deposition (CVD) method directly onto SiO 2 substrates at a relatively low substrate temperature (510–560°C). The temperature-dependent growth and evolution of MoS 2 nanodots and the local environment of sulfur-induced structural defects and impurities were systematically investigated by field emission scanning electron microscopy, micro-Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS) techniques. At the substrate temperature of 560°C, we observed mostly few-layer MoS 2 , and at 510°C, multilayer MoS 2 growth, as confirmed from the Raman line shape analysis. With reduced substrate temperature, the density of MoS 2 nanodots decreases, and layer thickness increases. Raman studies show characteristic Raman modes of the crystalline MoS 2 layer, along with two new Raman modes centered at ∼346 and ∼361 cm −1 , which are associated with MoO 2 and MoO 3 phases, respectively. Room temperature photoluminescence (PL) studies revealed strong visible PL from MoS 2 layers, which is strongly blue-shifted from the bulk MoS 2 flakes. The strong visible emission centered at ∼ 658 nm signifies a free excitonic transition in the direct gap of single-layer MoS 2 . Position-dependent PL profiles show excellent uniformity of the MoS 2 layers for samples grown at 540 and 560°C. These results are significant for the low-temperature CVD growth of a few-layer MoS 2 dots with direct bandgap photoluminescence on a flexible substrate.